Detrital zircon geochronology and sedimentology of glaciogenic strata of the middle Carboniferous San Eduardo Formation, Calingasta-Uspallata Basin, NW Argentina - Malone, John E. (2019)
The Calingasta-Uspallata Basin preserves a near continuous sequence of glaciomarine deposition from themiddle to late Carboniferous, represented by five separate formations. Correlation between theseformations have been achieved using index marine invertebrates, which also provides some implicationsfor max-depositional ages. However, no isotopic dating analyses have been sought in this basin to furtherconstrain the age of deposition or provide a source of provenance for sediments. The San Eduardoformation near the El Leoncito Astronomical Complex, San Juan Province, Argentina, was deposited withinthe Calingasta?Uspallata Basin on the western margin of the proto-Precordillera during the lateMississippian to early Pennsylvanian. This succession preserves a complete sequence of proximalglaciomarine, nearshore, and fluvial systems deposited at the beginning of the late Paleozoic ice age.Samples were collected from various stages throughout the sequence for detrital zircon U-Pbgeochronology to determine sediment provenance as a way of isolating different glacier sources. Resultsindicate multiple stages of glaciation, with at least three distinct source areas. The lowermost stageincludes locally sourced basement and recycled underlying Silurian, represented by similar Famatinian(500-460 Ma) and Sunsas peaks (1450-1000 Ma) peaks, with the Sunsas source likely originating from theWestern Sierras Pampeans, which would represent a breaching of the proto-Precordillera from the east.The middle stage shows a population distinct unto itself, with a peak during the Mississippian (330-360Ma). A volcanic island arc was situated along the Andean margin during the late Paleozoic, likely resultingin the influx of Carboniferous aged volcanic sediments. The lower most stage shows relations based on K-Sresults to formations within the Paganzo basin to the northeast, likely serving as the outwash of thesedistant glaciers through braided fluvial systems. This study will expand upon current chronologicknowledge within the Calingasta-Uspallata basin and will be supported by sandstone petrology andmineralogic composition, pebble counts and composition of dropstones.